Photo-CIDNP 1H-NMR studies of bovine pancreatic phospholipase A2 and its zymogen. - Egmond, MR; Hore, P; Kaptein, R (1983)
Bovine pancreatic phospholipase A2 and its zymogen were studied by laser photo-CIDNP 1H-NMR. Resonances of Trp3 and Tyr69 protons of the two proteins were assigned. By varying the delay between a short light pulse and the observation pulse, time dependencies of the CIDNP signals were obtained from which effective T1 values could be derived. The photo-CIDNP chemical shifts, intensities and relaxation data pointed to environmental differences for the Tyr69 residues in the two proteins, while only small differences were noted for the Trp3 residues. The more buried position of Tyr69 in the enzyme relative to the zymogen was related to the ability of the enzyme to bind to micellar aggregates, to which the zymogen is unable to bind.